Maximizing The Use of Internet-based Resources in Improving Listening Skill - Astiti Dwi Handayani (Pancaran Pendidikan, 2018)
Listening is sometimes regarded as a passive skill since it is receptive skill. Thus, the role of listening is not as crucial as other productive skills.Additionally, acquiring listening skill can be frustrating for some learners because they must put great effort of which is not easy to improve their listening skill. This eventually leads learners do not pay much attention to it. Whereas listening is considered to be the initial stage in learning languages. Give an understanding about the importance of listening in language learning is essential in order to give learnersopportunity to improve their listening skill. Therefore, this paper aims to share ideas of maximizing the use of ICT especially internet-based resourcesin improving listening skill. The benefits of the useof internet-based resources will be explained in order to help the learners improve their listening skill.